PENERAPAN TEKNOLOGI FORTIGATE DALAM PEMBANGUNAN JARINGAN VPN-IP BERBASIS IPSEC - Hari Suryantoro; Adi Sopian; Dartono Dartono (JEIS: Jurnal Elektro dan Informatika Swadharma, 2021)
IPSec based VPN (Virtual Private Network) is a standard that provides data confidentiality, data integrity, and source authentication on public communication such as the internet. IPSec VPN is a secure technology and reliable (secure and reliable) which can connect private networks between campuses using internet public communications. The availability of data and services in real-time is very much needed by the main campus to ensure that operational and business activities at branch campus and main campus run smoothly. FortiGate is the best choice for system security that provides high protection against threats dynamic security and simplifies the IT security infrastructure company. This study aims to build a VPN (Virtual Private Network) based on IPSec. The research was conducted on a Wide Area Network using two FortiGate devices as a firewall and gateways are connected to each other and form a tunnel as a special path connect private networks between campuses securely. The results showed that clients at branch campus can access servers located at the main campus in real-time, and data transfer performance between branch campus and main campus was successfully accepted, and getting bigger packets sent, the file transfer process time will also be longer.